Ellipsometric spectroscopy study of Ar ion-beam mixed SiO2/Si/SiO2 layers - Kim, HB; Son, JH; Whang, CN; Chae, KH (ELSEVIER SCIENCE BV, 2004)
Si layer between SiO2 layers has been changed from amorphous state to other state containing Si nanocrystals by ion beam mixing and subsequent annealing at high temperature in N-2, ambient. This change was measured by ellipsometric spectroscopy. The fitting of spectra was carried out using effective medium approximation model for the sample containing Si nanocrystals. The structural change of Si layer was confirmed by cross-sectional high-resolution transmission electron microscopy. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: VISIBLE PHOTOLUMINESCENCE; NANOCRYSTALLINE-SILICON; SI; RECRYSTALLIZATION; LUMINESCENCE; INTERFACE; FILMS